Ex Parte Relief in Emergency Arbitration: Protective Preliminary Orders under the 2025 Singapore Arbitration Centre (SIAC) Rules - Muhammad Ilham Agus Salim (Badan Arbitrase Nasional Indonesia, 2026)
This paper examines the emergence of ex parte interim relief in international arbitration, focusing on the introduction of Protective Preliminary Orders under Schedule 1, Rule 25 of the 2025 SIAC Arbitration Rules. Traditionally, arbitral tribunals have refrained from granting relief without notice due to concerns regarding party consent, due process, and enforceability. This study evaluates whether such concerns remain valid in light of recent institutional developments. It argues that the consent objection is overstated, as parties effectively accept procedural powers including ex parte measures through the incorporation of institutional rules into arbitration agreements. Similarly, the due process objection can be mitigated where the respondent’s right to be heard is deferred rather than denied, supported by safeguards such as short expiry periods and prompt inter partes hearings. However, the paper identifies the arbitrator’s lack of coercive power as a fundamental structural limitation. Unlike national courts, arbitral tribunals cannot compel third parties or enforce compliance through sovereign authority, limiting the practical effectiveness of ex parte relief in urgent situations involving asset dissipation or evidence preservation. A comparative analysis demonstrates that arbitral and judicial standards for granting interim relief are largely aligned in both procedural and substantive aspects. The paper concludes that while the 2025 SIAC Rules represent a significant advancement in arbitral practice, ex parte emergency relief cannot fully replace judicial intervention. Instead, it should be understood as a complementary mechanism, enhancing the flexibility and responsiveness of arbitration while preserving the essential role of national courts.